The effect of fertility control on soil conservation as a basic resource of sustainable agriculture - Vladanka STUPAR; Zlata ŽIVKOVIĆ; Aleksandar STEVANOVIĆ; Darko STOJIĆEVIĆ; Tatjana SEKULIĆ; Jelena Ž. BOŠKOVIĆ; Vera M. POPOVIĆ (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2024)
For agricultural production is used almost 40% of the global land from where it dominates conventional agriculture which uses large amounts of inputs in the form of fertilizers and pesticides leading to the contamination of soil, water resources, air pollution and land erosion, affects biodiversity and extinction of many plants and animals. On the other hand, the world's population is constantly growing and currently numbers more than 8 billion people and it is estimated that food production will have to double by 2050. In order to meet the future needs of the population for food raw materials, food production must significantly increase, and at the same time, the impact of agriculture on the environment and natural resources must be drastically reduced. Sustainable agriculture is emerging as one of the solutions. This way of agricultural practice refers to the management and preservation of natural resources through organizational and technological changes in modern agricultural production in order to satisfy human needs and preserve the environment. One of the most important natural resources on which the entire agricultural production relies is land. In intensively cultivated lands, there is a noticeable trend of intense degradation, which represents a major problem facing humanity. The paper reviews the decrease in soil fertility based on the samples collected during the five-year monitoring, as well as a proposal for measures to increase fertility and future preservation of this environmental resource.